Software Implementation for Evaluating Human Resources in the Legal Department within Companies in Technical Field. (2015) - Adrian, Mocanu; Mihai, Birsan; Angela, Repanovici
Abstract: The paper deals with the very particular issue of the legal departments functioning within companies working in technical fields. Besides engineering and management knowledge, these companies must bear with a strong juridical knowledge, incorporated in their activity. The authors propose a systemic perspective based on the concept of evaluation of the human resources as the foundation of development of the company. The originality of the work described here consists of the implementation of a computer program called MPSJ (Managementul Personalului din Sistemul Juridic) - Legal Personnel Management System – that can be applicable to the legal departments of the companies in order to determine the role of legal and managerial skills for continuous improving.